2010
DOI: 10.4314/jasem.v14i2.57871
|View full text |Cite
|
Sign up to set email alerts
|

Variability and Character Association in F2 Segregating Population of Different Commercial Hybrids of Tomato (<i>Solanum lycopersicum</i> L.)

Abstract: ABSTRACT:The F2 segregating generations of exotic tomato hybrids were studied to measure variability, character association and path coefficient analysis. Analysis of variance for each trait showed significant differences among the genotypes. Very little differences were observed between phenotypic coefficients of variation (PCV) and genotypic coefficients of variation (GCV) for the traits days to first flowering (pcv=9.21, gcv=7.82), fruit length (pcv=17.14, gcv=14.84) and fruit diameter (pcv=17.10, gcv=14.92… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
16
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 3 publications
20
16
2
1
Order By: Relevance
“…Analyzed data showed that variance of genotype (Vg) was lower than the variance of phenotype (Vp) in the F2 populations for all the traits under study. Same were the findings of Mohamed et al [12] and Gosh et al [13] except for fruit-length and fruit diameter in his study .In the F2 population higher difference was noted between Vg and Vp for the traits Flowers/cluster, Fruits/cluster, Fruit weight, fruits/ plant and Yield/plant while lower difference was found between Vg and Vp for the traits like Fruit diameter and Fruit length as shown in table-1. High difference between Vg and Vp indicates that environment has more contribution in the phenotypic appearance of the traits than their genetic make-up.…”
Section: Resultssupporting
confidence: 80%
“…Analyzed data showed that variance of genotype (Vg) was lower than the variance of phenotype (Vp) in the F2 populations for all the traits under study. Same were the findings of Mohamed et al [12] and Gosh et al [13] except for fruit-length and fruit diameter in his study .In the F2 population higher difference was noted between Vg and Vp for the traits Flowers/cluster, Fruits/cluster, Fruit weight, fruits/ plant and Yield/plant while lower difference was found between Vg and Vp for the traits like Fruit diameter and Fruit length as shown in table-1. High difference between Vg and Vp indicates that environment has more contribution in the phenotypic appearance of the traits than their genetic make-up.…”
Section: Resultssupporting
confidence: 80%
“…Heritability coefficient was found to be high for all studied traits including yield/ Plant and its components under heat stress condition (Rashwan, 2016). Similar values of heritability were also noticed by several authors among them (Ghosh 2010;Jiregna et al 2011;Kamel et al 2010).…”
Section: Introductionsupporting
confidence: 86%
“…The number of fruits per plant (0.753, 0.855) had highest positive direct effect on the fruit yield followed by average fruit weight ( Number of fruits per plant exhibited positive direct effect on fruit yield as reported by Singh et al, (2006), Ara et al, (2009), Ghosh et al, (2010 and Ullah et al, (2015). Similarly, Singh et al, (2006), Ara et al, (2009), Dar et al, (2011 and Tiwari et al, (2013) also reported that average fruit weight exerted positive direct effect on fruit yield.…”
Section: Resultsmentioning
confidence: 73%